Response to the comment on "The role of the depth of invasion (DOI) in minor salivary glands tumors according to the 8th TNM classification: Pitfalls and potential misinterpretations". (September 2022) - Calabrese, Luca; Nocini, Riccardo; Spirito, Francesca; Gazzini, Luca; Dallari, Virginia; Girolami, Ilaria; Lo Muzio, Lorenzo
Highlights: DOI is an indirect measure of neurovascular and lymphatic structures involvement. A plenty of genetic mutations must be present for tumour advancement and spreading. OSCC invading the basement membrane is presumed to have the spreading capacity. Further studies are needed to define the role of DOI in different oral carcinoma histotypes.